Hydraulic and hydrological system simulation of the Rímac-Santa Eulalia River basin - Sarango, D. D. (2014)
This research aims to develop a simulation model, for the operation of hydraulic and hydrological system of the Rima-Santa Eulalia River basin that includes the H. P. Huanza project now in construction, with purposes of power generation, water supply for agricultural use and drink water for population of Lima and Callao. The hydraulic system is formed by hydroelectric EDEGEL S.A. that operate using the regulated and unregulated flow of the Santa Eulalia river basin, Rímac river basin, Marcapomacocha Lake watershed and flows into the tunnel Trasandino infiltrators. We evaluated the operation of the project H. P. Huanza located upstream Sheque reservoir, in order to not affect the operation of H. P. Huinco EDEGEL property. The results obtained from the simulation model are acceptable for guaranteeing an average flow rate of 12.51 m3/s to be used by the H. P. Huinco and we can count on 95 % of simulated time period 1978-2005 with a flow rate of 25.0 m3/s in Chosica Station, to cover agricultural, population and ecological demand of Lima and Callao Provinces . The simulation model developed could be used by EDEGEL, ANA, MINAG, SEDAPAL and SENAMHI to evaluate other hydroelectric projects, irrigation and drinking water supply in the Rímac-Santa Eulalia river basin.